The Millennium Eruption of Changbaishan Tianchi Volcano is VEI 6, not 7 - Yang, Q; Jenkins, SF; Lerner, GA; Li, W; Suzuki, T; McLean, D; Derkachev, AN; Utkin, IV; Wei, H; Xu, J; Pan, B (Springer, 2021)
The Millennium Eruption (AD 946–947) of Changbaishan Tianchi Volcano is one of the largest known eruptions in recorded history. With the help of previously published isopachs and distal ash thicknesses, we re-calculate the bulk volume of its distal eruptive product, the B-Tm ash, as 27–62 km3 and the total eruption volume as 40–98 km3. The updated volume estimates are around half of those estimated by previous studies of this seminal eruption. Our work shows that the Millennium Eruption is a VEI-6 eruption, rather than VEI-7 as previously envisaged, and its magnitude is also lower than previously thought. This has implications for regional frequency-magnitude relationships and may also partially explain the limited regional, rather than global, climatic effects of the Millennium Eruption.